Preparation and Characterization of Rare Earth-Doped Ti/SnO2-Sb-Mn Electrodes for the Electrocatalytic Performance. (16th May 2020) - Wai, Thet Phyo; Yin, Yilin; Zhang, Xiao; Li, Zenghe
Abstract : The modified Ti/SnO2 -Sb-Mn/Re electrodes were prepared using rare earth (Re) Gd, Eu, Ce, and Er and various molar ratios of tin and manganese by thermal decomposition. To investigate the electrocatalytic performance of electrodes, phenol was applied as a model pollutant. Phenol removal pursued pseudofirst-order kinetics in the experimental range. The experimental outcomes show that the phenol degradation at ~95% and ~97% was found in Mn (1 mol%)/Re and Mn (2 mol%)/Re electrodes after treatment for 140 min. Accelerated lifetime testing showed that the best-accelerated service life could be measured only in Mn (3 mol%)/Re and Mn (4 mol%)/Re compared with other prepared Mn (0%, 1%, and 2%)/Re electrodes under the condition of 500 mAcm -2 current density in this study. The modified electrodes were then characterized, including oxygen evolution potential (OEP), crystal structure, and surface composition of the electrode coatings.